New species and records of Geodromicus Redtenbacher, 1857 from China (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Cheng, Zhi-Fei; Shavrin, Alexey V.; Peng, Zhong (Zootaxa, 2020)
New diagnostic, taxonomic and faunistic data for 17 species of the genus Geodromicus Redtenbacher, 1857 from China are provided. Five species are (re-) described and illustrated: G. magnus Shavrin sp. n. (Shaanxi), G. namucuoicus Cheng & Peng, sp. n., G. subquadratus Cheng, Shavrin & Peng sp. n. (Xizang Autonomous Region), G. paramerus Shavrin, 2000, and G. shii Cheng & Peng sp. n. (Neimenggu and Ningxia autonomous regions, Shanxi). Geodromicus frigidus Smetana, 1968 is recorded from North Korea, G. hammondi (Watanabe, 1990) and G. paramerus from China for the first time. To date, 22 species of Geodromicus are reliably known from China. A key to the species known from China and distribution maps for all species are provided.